Turbulence characteristics of the I-mode confinement regime in ASDEX Upgrade. (29th June 2017) - Manz, P.; Happel, T.; Ryter, F.; Bernert, M.; Birkenmeier, G.; Conway, G.D.; Dunne, M.; Guimarais, L.; Hennequin, P.; Hetzenecker, A.; Honoré, C.; Lauber, P.; et al.
Abstract: Besides strong geodesic acoustic mode (GAM) activity, turbulence in the I-mode confinement regime of ASDEX Upgrade exhibits two prominent features, the weakly coherent mode (WCM) and strongly intermittent solitary density perturbations. The nonlinear interaction between these structures is studied in detail by means of a conditional averaged wavelet-bicoherence analysis. The wavelet analysis reveals that these density perturbations are at the WCM frequency. The GAM is coupled to all frequency scales of the velocity fluctuations via a modulational instability. The WCM shows coupling to higher frequencies prior to the bursts, indicating a process resembling wave-steepening. A possible mechanism for the generation of such solitary density perturbations by a Korteweg–de Vries-like nonlinearity is discussed.